Bevacizumab and neovascular age related macular degeneration - El Mollayess, Georges (2011)
The pathogenesis of neovascular age related macular degeneration (AMD) is multifactorial including inflammation and angiogenesis leading to choroidal neovascularization (CNV). Therapy against vascular endothelial growth factor (VEGF) has revolutionized the treatment of neovascular AMD. Intravitreal off-label use of bevacizumab proved to be safe. This literature review was conducted to study improvement in visual acuity, change in central retinal thickness (CRT), safety, pharmacodynamics, and possible resistance to intravitreal bevacizumab over a one-year period in eyes with neovascular AMD. We reviewed articles between 1997 and January 2010 that included at least 30 patients with AMD who received intravitreal bevacizumab monotherapy for at least 1 year. The mean number of letters gained, decrease in CRT, and number of injections were 8 letters, 125.3 µm, and 4.3 injections, respectively. Further, randomized prospective clinical trials are needed to determine the efficacy and safety of intravitreal bevacizumab in the treatment of neovascular AMD.